SISTEM PENYIRAMAN TANAMAN TOMAT OTOMATIS BERBASIS ARDUINO UNO DAN PANEL SURYA - Dzalfa Zahrotun Nisa; Arnisa Stefanie (Politeknik Harapan Bersama Tegal, 2023)
Abstract − As time goes by, technological developments are increasing, so that it can provide many conveniences for humans to do daily work such as caring for tomato plants. In the process of caring for plants, water is needed for plant growth, besides that water is also used in the process of photosynthesis, water is used by plants to dissolve minerals that are absorbed by roots from the soil as a process of plant development. Watering plants regularly can maintain and care for plants so they can grow well. Watering plants automatically using Arduino Uno and solar panels allows humans to control and monitor plant watering devices. The results of this study show that the automatic plant watering system using Arduino Uno and solar panels works well. This research aims to make it easier for farmers in the process of watering tomato plants and to make it easier for farmers to control plants. So that negligence in watering plants can be avoided, and plants can grow optimally with water intake that is given automatically. The results of the study show that the automatic plant watering system works well and is able to monitor the condition of water content in the soil. Keyword− arduino uno, solar panel, watering